P3.313 Comparison of Psychopathological Dimensions in Substance Abusers with and Without HIV/AIDS and Healthy Matched Group. (13th July 2013) - Taramian, S; Rezaei, S; Kafi, M; Pooragha, F; Bazarganian, N
Abstract : Background: Inattention to symptoms of mental disorders and substance abuse in patients with HIV/AIDS and other at risk groups, may lead to irreversible damages. Present research aimed at comparison of psychopathological dimensions in substance abusers with and without HIV/AIDS and healthy matched groups. Methods: In a cross-sectional and analytical study, selected samples by available, consecutive, and objective methods were 43 HIV positive substance abusers, 49 HIV negative substance abusers under Methadone Maintenance Therapy (MMT) in counselling clinic of behavioural diseases and addiction abandonment and 45 ordinary individuals. All of them were evaluated by matched confounding variables via symptom check list-90-Revised (SCL-90-R). Results analysed by chi-square (χ 2 ), independent t test, one-way analysis of variance (ANOVA) and Gabriel post hoc. Results: Findings indicated significant difference between these groups in Global Severity Index (GSI), Positive Symptom Distress Index (PSDI) and Positive Symptom Total (PST) (P < 0.0001). Two by two comparison of the three groups from psychopathological dimensions revealed that substance abusers with HIV/AIDS persistently suffer more mental problems in all dimensions compared with healthy ones (P < 0.05) and in other dimensions including somatization, interpersonal sensitivity, depression, anxiety, phobia, and psychoticism in comparison with HIV negative substance abusers (P < 0.05). Yet, the difference in paranoid ideation, hostility and obsessive-compulsive case was insignificant. Two by two comparison of healthy ones and substance abusers without HIV/AIDS showed higher levels of depression and Psychoticism in substance abusers (P < 0.05) but no difference in other dimensions. Conclusion: Comorbidity of substance abuse and HIV diagnosis intensify mental disorders symptoms. Moreover, lack of prevention and implementation of appropriate psychological and psychiatric interventions after substance abuse and HIV lead to extended establishment of mental disorders symptoms. Some implications of these results are discussed results may direct future researches.